Clause chaining and conjugations in Wolof: a typology of parataxis and its semantics - (:unkn) unknown (My University, 2010)
Due to the specificity of its verb conjugation system, Wolof (Senegal) favors parataxis for clause combining and provides an interesting case where interclausal dependency can be marked by forms indicating information hierarchy. Furthermore, the study of clause combining shows that, with some restrictions on possible combinations, the various combinations of conjugations (or Tense-Aspect-Modality markers) produce different but regular interclausal meanings, such as succession, causality, opposition or consecution. Moreover, due to the nature of the different conjugations, paratactic clause chaining in Wolof yields different types of interclausal dependency, defining a gradient of syntactic integration: from simple assertive juxtaposition to more integrated syntactic dependency, through lesser known types of dependency, defined here as ‘situational dependency' and ‘pragmatic dependency'.
Keywords: African Research